PENGARUH PENGETAHUAN DAN MOTIVASI KERJA PPKBD TERHADAP KINERJA DAN KETAHANAN KELUARGA - Faisal, Willy; Zubaidi, Ahmad; Ikhwan, Hakimul (Universitas Muhammadiyah Surakarta, 2019)
The aim of this research are (1) to determine the effect of knowledgeon the performance of rural family planning officer of Semarang District (PPKBD) (2) to determine the effect of work motivation on the performance of Semarang District PPKBD (3) to deter mine the influence of knowledge on Family Resilience in Semarang District (4) to determine the effect of work motivation towards Family Resilience in Semarang District (5) to determine the effect of PPKBD's performance on Family Resilience in Semarang Regency. The population used in this study were all members of the Semarang District PPKBD. Based on the sample calculation, the resultsobtained were 148 members of PPKBD as respondents. Data Analysis Techniques used are Descriptive Analysis, Inferential Analysis, and Path Analysis Model Testing. Based on the results of the testing revealed that all hypothesis were accepted